Pleural tumours and tumour-like lesions. Issue 12 (December 2018) - Aluja Jaramillo, F.; Gutierrez, F.; Bhalla, S.
Abstract : There are various neoplasms and tumour-like conditions of the pleura. Mesothelioma is perhaps the most widely recognised; however, there are many others that are more common and should be considered. Understanding the similarities and differences can be helpful in managing the patient with a newly found pleural lesion. We will discuss clinical symptoms at presentation and describe the imaging findings associated with these tumours, starting with conventional radiology, and correlating with computed tomography and combined positron-emission tomography (PET)/computed tomography (CT). Finally, imaging characteristics that help differentiation between the benign and malignant varieties will be reviewed.